2018
DOI: 10.1080/13557858.2018.1495320
|View full text |Cite
|
Sign up to set email alerts
|

An indigenous framework of the cycle of fetal alcohol spectrum disorder risk and prevention across the generations: historical trauma, harm and healing

Abstract: Effective, multiple-level FASD prevention approaches for AI/ANs may include prioritizing Indigenous culture, supporting intergenerational cohesion, focusing on non-stigmatic healing of traumas, and authentically engaging community knowledge. This work draws on community and cultural strengths in an effort to reduce the occurrence of substance-exposed pregnancies, and encourages transformational changes in systems that serve AI/AN peoples to promote a healthy and thriving community and future generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 40 publications
5
59
0
Order By: Relevance
“…The cornerstone of these approaches is the concept of historical trauma. Successive sociopolitical and genocidal acts disrupted the cohesion of AI families, communities, and government systems (Brave Heart, 1998; Duran & Duran, 1995; Evans-Campbell, 2008; Gone, 2009; Gracey & King, 2009; Gonzales et al, 2018; Graham, 2008; Sarche, Tafoya, Croy, & Hill, 2017; Whitbeck, Hoyt, McMorris, Chen, & Stubben, 2001; Whitbeck, Adams, Hoyt, & Chen, 2004; Wilkins & Stark, 2011). Cumulative effects related to colonial terrorism went unresolved and traversed generations, resulting in complex, unresolved grief and loss, survivor guilt, psychic numbing, fear, anger, and other symptoms (Balestrery, 2016; Gonzales et al, 2018; Kading et al, 2015; Whitbeck, Chen, Hoyt, & Adams, 2004; Brave Heart, 1999), also summarized as a “soul wound” (Duran & Duran, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cornerstone of these approaches is the concept of historical trauma. Successive sociopolitical and genocidal acts disrupted the cohesion of AI families, communities, and government systems (Brave Heart, 1998; Duran & Duran, 1995; Evans-Campbell, 2008; Gone, 2009; Gracey & King, 2009; Gonzales et al, 2018; Graham, 2008; Sarche, Tafoya, Croy, & Hill, 2017; Whitbeck, Hoyt, McMorris, Chen, & Stubben, 2001; Whitbeck, Adams, Hoyt, & Chen, 2004; Wilkins & Stark, 2011). Cumulative effects related to colonial terrorism went unresolved and traversed generations, resulting in complex, unresolved grief and loss, survivor guilt, psychic numbing, fear, anger, and other symptoms (Balestrery, 2016; Gonzales et al, 2018; Kading et al, 2015; Whitbeck, Chen, Hoyt, & Adams, 2004; Brave Heart, 1999), also summarized as a “soul wound” (Duran & Duran, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Successive sociopolitical and genocidal acts disrupted the cohesion of AI families, communities, and government systems (Brave Heart, 1998; Duran & Duran, 1995; Evans-Campbell, 2008; Gone, 2009; Gracey & King, 2009; Gonzales et al, 2018; Graham, 2008; Sarche, Tafoya, Croy, & Hill, 2017; Whitbeck, Hoyt, McMorris, Chen, & Stubben, 2001; Whitbeck, Adams, Hoyt, & Chen, 2004; Wilkins & Stark, 2011). Cumulative effects related to colonial terrorism went unresolved and traversed generations, resulting in complex, unresolved grief and loss, survivor guilt, psychic numbing, fear, anger, and other symptoms (Balestrery, 2016; Gonzales et al, 2018; Kading et al, 2015; Whitbeck, Chen, Hoyt, & Adams, 2004; Brave Heart, 1999), also summarized as a “soul wound” (Duran & Duran, 1995). These outcomes continue to amalgamate with direct, contemporary stressors (e.g., microaggressions, lateral oppression), resulting in behavioral and physical health sequelae (Balestrery, 2016; Brave Heart, 2000; Brave Heart, Chase, Elkins, & Altschul, 2011; Brockie, Heinzelmann, & Gill, 2013; Burnette & Figley, 2017; Gonzales et al, 2018; Brave Heart, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Culturally responsive healthcare programming is an approach that holds promise in alleviating the impact of these healthcare inequities and may actually help to improve patient engagement, adherence to healthcare recommendations, and subsequent health outcomes. However, we also note that among AI/ANs, issues of poor retention patient engagement are evidenced even in programming that is culturally responsive . Together, these factors complicate the ability for AI/AN communities to practice consistent GDM risk reduction behaviors and effectively benefit from GDM risk reduction and PC education resources .…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, a legacy of RH choice restriction for AI/AN women, including sterilization without consent, contributes to a deep mistrust of RH programming, making cultural tailoring of any RH counseling of particular importance for AI/AN females. Knowledge of this legacy and concern about being stereotyped and stigmatized by medical care providers has led to disengagement with healthcare by AI/AN women, and these issues are relevant for RH . Prior research has also consistently documented that this distrust is may be influenced and perpetuated by implicit and/or explicit bias among healthcare providers and institutional racism within healthcare organizations and respective RH healthcare systems .…”
Section: Introductionmentioning
confidence: 99%
“…Health behaviors of AI/AN men, including recruitment and retention patterns in health interventions, exist in the context of historical, intergenerational, and contemporary experiences of colonization and colonial trauma responses ( Evans-Campbell, 2008 ; Gonzales et al, 2018 ; Paradies, 2016 ). Numerous studies with AIs/ANs show that psychosocial stress responses to colonial trauma may have important impacts on retention, health-care utilization, and achievement of therapeutic outcomes promoted in health interventions ( Gonzales et al, 2014 , 2018 ; Jacob et al, 2015 ; Walls & Whitbeck, 2012 ). A recent study conducted among AIs/ANs enrolled in a culturally informed diabetes prevention program demonstrated that colonial trauma adversely impacted retention and intervention outcomes (Gonzales, forthcoming) ( Gonzales et al, forthcoming ).…”
mentioning
confidence: 99%